Relevansi Sufi Healing dengan Konsep Flourishing terhadap Perilaku Bunuh Diri - Wijanarko, Aisyah Aprilya (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
The global suicide mortality rate is increasing. The high rate of suicide necessitates the enhancement of interventions that integrate aspects of spirituality and psychological well-being, specifically the concepts of Sufi healing and flourishing explored in this study. The research problem encompasses two main points: 1) how is suicidal behavior viewed within the framework of flourishing in positive psychology and Sufi healing? and 2) what is the relevance of flourishing elements to Sufi healing in the context of suicide prevention? This study aims to explore the relevance of the concept of flourishing in positive psychology and Sufi healing in the context of suicide prevention. The research method used is a qualitative approach with in-depth literature analysis. Data analysis was conducted by identifying key themes related to the research topic. The results show that 1) elements of flourishing such as meaning in life, optimism, and social connectedness play a significant role in preventing suicidal behavior. Furthermore, 2) Sufi healing practices integrated with flourishing elements can strengthen psychological and social factors as protective measures against suicide. This research provides significant theoretical and practical contributions in the field of mental health, particularly in the development of interventions based on spirituality and positive psychology for suicide prevention.